If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 2x = 8x + -3 Combine like terms: 7x + 2x = 9x 9x = 8x + -3 Reorder the terms: 9x = -3 + 8x Solving 9x = -3 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 9x + -8x = -3 + 8x + -8x Combine like terms: 9x + -8x = 1x 1x = -3 + 8x + -8x Combine like terms: 8x + -8x = 0 1x = -3 + 0 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| 6f+5+75+35=180 | | -4x-2y-3z=-1 | | .25x+.10y=.19 | | X-24=-6 | | 5m-3-3m+5=26 | | 8x^3-3x^2+48x-18= | | 2x=14z-4xy | | 22+10x= | | 36x+3000=7500 | | 3x-7y-14z=0 | | -y(x-y+8)= | | 3X+200=350+X | | 4x+17+80+x+23=180 | | 3x+3x+6x+6=5x-30 | | 3x^4+7x^3-9= | | 4p-24=-13p-27 | | logx^3+2log^2-14=0 | | 4p-24=-3p-27 | | lgx^3+2lg^2-14=0 | | Ln(2x-6)+5=6 | | -4.2u+5.5=5.4u-4.1 | | 3(4x+5)-5(2x+3)=22 | | Ln(2x-6)-5=5 | | 5[3y+12]=6[5y+20] | | H=-5t^2+40t+10 | | -128+9p=3p-27 | | -2x-3zx=1-10y | | -128+9p=-3p-27 | | 2x+27x+15= | | 4*-7=41 | | y=15-4i | | 4(Y+22)+1=-5(3-2Y) |